Effect of Drying Temperature on Cyanogenic Glucoside Content and Physicochemical Properties of Hanatee Cassava Flour Compared with Commercial Cassava Flour - Khumkhom, Supichaya; Sangnark, Arpathsara; Kongsil, Pasajee; Siriwong, Nongnuch (Journal of Food Health and Bioenvironmental Science, 2024)
The impact of drying temperature on the cyanogenic glucoside content and physicochemical properties of Hanatee (HNT) cassava (Manihot esculenta Crantz) flour was compared with that of commercially available cassava flour (CCF). This investigation focused on flour derived from the HNT variety subjected to drying temperatures of 50, 60 and 70°C. A comprehensive analysis of both HNT and CCF flours were conducted to assess their proximate compositions, cyanide concentrations, colorimetric properties, water absorption index, swelling power, solubility, pasting characteristics and thermal properties. Moisture, carbohydrate, protein, lipid, ash, crude fiber and amylose contents of HNT cassava flour ranged at 4.63-10.54, 95.08-98.68, 1.14-1.54, 0.03-0.28, 0.11-3.22, 2.55-4.34 and 13.86-15.96%, respectively. While cassava cyanide contents ranged from 59.41-63.01 and 0.72-1.93 mg HCN/kg for roots and flours, respectively. Drying reduced hydrogen cyanide (HCN) concentration from 96.67% to 98.17%. Fresh cassava roots of the Hanatee variety processed into flour and dried at 50, 60 and 70oC showed reduced cyanide content within the international standard of 10 mg HCN/kg. The whiteness index of commercial cassava flour (39.72–41.98) was higher than HNT flour dried at different temperatures (32.40-39.72). Degrees of lightness (L*) ranged between 88.36 and 90.60, yellowness (b*) 7.92-11.84 and redness (a*) 0.74-1.46. The water absorption index, swelling power and solubility of HNT flour samples increased at higher drying temperatures. By contrast, the CCF samples demonstrated the highest values across these parameters. Flour pasting behavior was examined using a Rapid Visco Analyzer (RVA). Peak viscosity values of different cassava flours ranged from 144.06 to 271.41 RVU, with the CCF2 sample registering the highest value and the HNT50 sample giving the lowest. All cassava flour samples displayed higher paste viscosities than their respective pasting temperatures, which ranged from 70.68 to 77.14°C. Variations in thermal properties were influenced by protein retention. The HNT70 flours exhibited the highest peak viscosity, final viscosity and pasting temperature, while also demonstrating a lower tendency for retrogradatio n compared with HNT50 flours. Results showed that good quality HNT flour was produced after drying at 60°C. The information gained from this study can be used to increase the industrial potentials of flour from cassava roots.